2011
DOI: 10.1016/j.ijgo.2011.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Single-institute experience, management, success rate, and outcome after external cephalic version at term

Abstract: ECV was found to be a safe procedure at term. The skill of the physician significantly affected the success rate. The rate of surgical delivery after successful ECV was low. A trial of ECV at term and beyond is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
(22 reference statements)
2
13
0
Order By: Relevance
“…Our study demonstrated that physicians performing more procedures over the 3.5‐year study period had higher success rates. This finding was consistent with the results of a previous study examining factor leading to successful external cephalic version in Austria . Our study was not designed to determine how many procedures precisely were needed to attain or maintain competence; however, a study geared toward creating standards for midwives performing the procedure suggested a target of 30 or more procedures annually …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study demonstrated that physicians performing more procedures over the 3.5‐year study period had higher success rates. This finding was consistent with the results of a previous study examining factor leading to successful external cephalic version in Austria . Our study was not designed to determine how many procedures precisely were needed to attain or maintain competence; however, a study geared toward creating standards for midwives performing the procedure suggested a target of 30 or more procedures annually …”
Section: Discussionsupporting
confidence: 89%
“…This finding was consistent with the results of a previous study examining factor leading to successful external cephalic version in Austria. 26 Our study was not designed to determine how many procedures precisely were needed to attain or maintain competence; however, a study geared toward creating standards for midwives performing the procedure suggested a target of 30 or more procedures annually. 27 Hospitals may benefit from having a subgroup of providers performing external cephalic version to maintain and hone the skill.…”
Section: Gestational Age At Diagnosis Of Breech Presentationmentioning
confidence: 99%
“…As the authors mention in the limitations section, it is well established that the operator's skill is an important predictor of ECV outcome. 3 In addition, the authors examined the factors associated with ECV success rate. All factors examined in this large cohort were non-modifiable (parity, body mass index, placental location, etc.).…”
Section: Sirmentioning
confidence: 99%
“…Numerous national organisations, such as the Royal College of Obstetricians and Gynaecologists [1], Royal Australian and New Zealand College of Obstetrics and Gynaecology [4], and the American College of Obstetricians and Gynaecologists [5] recommend that all women with a breech presentation at 35–42 weeks of gestation should be offered an ECV. Hutton et al [6] conducted an international multicentre randomised controlled trial studying the timing of ECV and concluded that early ECV (defined as 34-35 weeks) increases the likelihood of cephalic presentation at birth but does not reduce the rate of caesarean section and may increase the risk of preterm birth, whereas other studies including Gottvall and Ginstman [2] and Bogner et al [7] have demonstrated that ECV at term reduces the risk of caesarean section.…”
Section: Introduction and Hypothesismentioning
confidence: 99%